Der Erwählte - Mann, Thomas 1875-1955 (Frankfurt am Main Fischer, 1974)
'The Holy Sinner' or 'Der Erwählte' was first published in 1951. It is based on the medieval verse epic Gregorius written by the German Minnesinger Hartmann von Aue (c. 1165–1210). The book explores a subject that fascinated Thomas Mann to the end of his life – the origins of evil and evil's connection with magic. Here Mann uses a medieval legend about "the exceeding mercy of God and the birth of the blessed Pope Gregory" as he used the biblical account of Joseph as the basis for Joseph and His Brothers, illuminating with his ironic sensibility the notion of original sin and transcendence of evil.
Paul Thomas Mann (1875-1955) was a German novelist, short story writer, social critic, philanthropist, essayist, and the 1929 Nobel Prize in Literature laureate. His highly symbolic and ironic epic novels and novellas are noted for their insight into the psychology of the artist and the intellectual.
Keywords: 20th Century (1901-2000); Literature; Novel; Religion